Efficiency and sustainability: an economic, social, environmental and sustainable analysis of sugar cane mills in São Paulo - Dotta e Silva, Gabriel Malta Campos [UNESP]; Périco, Ana Elisa [UNESP] (FapUNIFESP (SciELO), 2022)
Concerns regarding environmental footprint have been the key in sustaining the relationship between competitiveness and sustainability in a changing capitalist context. Brazil has a solid level of heterogeneity in the efficiency of its production chains due to its legal and political characteristics. The Brazilian sugar-energy sector poses a strong influence on the economy, it is the pioneer in replacing the use of fossil fuels for renewable sources, and it is a sector marked by chain efficiency differences. In this context, this study aims to analyze the efficiency of the sugar cane mills in the state of Sao Paulo, from 2007 to 2016, from an economic, social, environmental, and sustainable point of view. Data Envelopment Analysis (DEA) is used to generate robust and complete efficiency models. Large-classified plants were ranked with economic efficiency, due to economies of scale, and small-classified plants ranked benchmarks in the social and environmental analysis, showing that the operational size bias is not necessarily a prerequisite to rank benchmark units. Finally, it was seen a preponderance of small and large-classified mill plants, along with ethanol-classified plants, in the sustainable benchmark ranking.
Eficiência e sustentabilidade: uma análise econômica, social, ambiental e sustentável das usinas paulistas de cana-de-açúcar
Keywords: análise envoltória de dados; data envelopment analysis; efficiency; eficiência; setor sucroenergético; sugarcane sector; sustainability; sustentabilidade